High Risk of Conversion to THA After Femoroacetabular Osteoplasty for Femoroacetabular Impingement in Patients Older than 40 Years. Issue 5 (May 2021) - Yacovelli, Steven; Sutton, Ryan; Vahedi, Hamed; Sherman, Matthew; Parvizi, Javad
Abstract: Background: Femoroacetabular impingement (FAI) is a recognized cause of hip pain and decreased quality of life and has been linked to primary idiopathic hip osteoarthritis (OA). Although the operative indications for FAI have expanded to include older patients, we do not know whether there is an increased risk of conversion to THA after femoroacetabular osteoplasty (FAO) via the mini-open approach for FAI in patients older than 40 years compared with younger patients, after controlling for other confounding variables. Questions/purposes: (1) After matching for gender, BMI, preoperative symptomatic period, surgeon experience, Tönnis grade, and degree of chondral lesion, are patients older than 40 years who undergo FAO for FAI more likely to be revised to THA at a minimum of 2 years' follow-up than are patients younger than 40? (2) Is there a difference in delta (postoperative minus preoperative) improvement in functional outcome scores in those patients who did not go on to THA between patients older than and younger than 40 years? Methods: Between 2003 and 2017, one surgeon performed 281 FAOs via the mini-open approach in patients older than 40 years and 544 of the same procedure in patients younger than 40 years. During that period, the general indications for FAO were the same in both age groups: (1) history and physical exam consistent with FAI, (2) radiographic evidence of focal impingement (cam, pincer, or both), (3) evidence of labral or chondrolabral tears, and (4) minimal to no arthritic changes (all four criteria required). In general, age was not used as a contraindication for surgery. A total of 86% (241 of 281) of patients older than 40 and 91% (494 of 544) of those younger than 40 were available for minimum of 2 years' follow-up, had complete datasets (radiographs as well as preoperative and most recent patient-reported outcomes scores) at a minimum of 2 years after surgery, and were considered eligible for the match. Propensity score matching was used to match for BMI, gender, preoperative symptomatic period, surgeon experience, Tönnis grade, and degree of intraoperative chondral lesion. We matched at a 1:2 ratio 130 patients older than age 40 with 260 patients younger than age 40. The mean ± SD follow-up duration for both groups was 5 ± 2 years. The mean age of the cohort of interest was 47 ± 5 years compared with 28 ± 7 years in the control. Fifty-four percent (70 of 130) of patients older than 40 years were women and 46% (60 of 130) were men; for those younger than 40, 51% (133 of 260) of participants were women and 49% (127 of 260) were men. Tönnis grade distribution for patients older than 40 was as follows: 46% (60 of 130) had Grade 0, 42% (55 of 130) had Grade 1, and 12% (15 of 130) had Grade 2. In comparison, Tönnis grade for patients younger than 40 was as follows: 52% (136 of 260) had Grade 0, 38% (100 of 260) had Grade 1, and 9% (24 of 260) had Grade 2 (p = 0.49). Chondral lesion degree was determined intraoperatively as none, a partial-thickness tear, or a full-thickness tear. Tönnis grade was determined based on preoperative plain AP hip radiographs. We then compared the percentage of patients who converted to THA during the surveillance period (our primary study outcome). We also compared the difference in delta (preoperative minus postoperative) improvement in functional outcome scores using the modified Harris Hip Score (mHHS) between the groups, excluding those who had already been converted to THA. Results: In patients older than 40 years, 16% (21 of 130) converted to THA at a mean time to conversion of 2 ± 1 years compared with 7% (17 of 260) at a mean time of 2 ± 2 years in patients younger than 40 years (p = 0.01). At a mean of 5 ± 2 years after FAO, among those patients who had not undergone conversion to THA, the mean delta mHHS score for patients older than 40 was 11 ± 17, compared with 20 ± 26 for patients younger than 40 (p = 0.04). Conclusion: Since approximately 1 in 6 patients older than 40 years in this series who underwent FAO for FAI opted for early conversion to THA at a mean time of 2 years after the osteoplasty procedure, and the remaining patients who did not undergo THA reported lower improvement in functional outcomes, we recommend surgeons avoid this procedure in patients in this age group until or unless we can better refine our indications. This is especially true because loss to follow-up causes us to believe that, if anything, our estimates of the risk of conversion to THA are conservative. Level of Evidence: Level III, therapeutic study.